Faktor-Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Dika Febriana; Astuning Saharsini (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to determine the influence of company size, profitability, leverage and financial distress on earnings management in insurance companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. This research method is a quantitative method using secondary data. The population in this study were all insurance companies listed on the Indonesia Stock Exchange (BEI), 18 insurance companies listed on the IDX in 2019-2022, by taking samples using a purposive sampling method to obtain a sample of 11 companies. The data analysis techniques used are descriptive statistics, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this research show that profitability partially influences earnings management, while company size, leverage and financial distress do not influence earnings management.